Heritability estimates of weaning weight of rabbits in commercial rabbit farm in Selangor, Malaysia. - Nur Amira Hani Faris Rafidi, author.
A retrospective study in 2020 was conducted on a commercial rabbit farm in Selangor, Malaysia on the weaning weight of New Zealand cross Hycole rabbit. This study aimed to estimate heritability and to evaluate the influence of environmental factors on the weaning weight of rabbits. A total of 27 data was being recorded and analysed. The analysis was done using Windows-based statistical package viz. Microsoft Excel and IBM SPSS statistics version 25. Parent-offspring regression method was used to estimate heritability while the environmental factors were measured using linear regression analysis. The average weaning weight for New Zealand cross Hycole kit was 572.824 ± 51.46g. The age of dam and body weight of dam did not significantly (p<0.05) influence the weaning weight of rabbits. The heritability of weaning weight and litter size was estimated to be -0.65 and -33 which is negatively correlated. In overall, genetics and environmental factors do not affect the weaning weight of a rabbit. The result obtained from this study was largely influenced by the small sample of data and lack of parameters of the environmental factors. Hence, a larger sample of data is needed for future study. Furthermore, the field of study could be expanded by using other traits and compare with different types of breed and more environmental factors are required and need to be included in order to obtain a better result.